A Case Report of Bilateral Mirror Clubfeet and Bilateral Hand Polydactyly - Nguyen, Mai P (The University of Iowa, 2014)
We report a rare case of a patient with bilateral mirror clubfeet and bilateral hand polydactyly. The patient presented to our orthopaedic clinic with bilateral mirror clubfeet, each with eight toes, and bilateral hands with six fingers and a hypoplastic thumb. The pattern does not fit any described syndrome such as Martin or Laurin-Sandrow syndrome. Treatments by an orthopaedic pediatric surgeon and an orthopaedic pediatric hand surgeon are described. The patient achieved excellent functional and cosmetic outcomes at four year follow-up.